Synthesis, characterization and catalytic investigations of Pt-based binary (bimetallic) and ternary (trimetallic) nanoparticles - Leteba, Gerard Malefane (Department of Chemical Engineering, 2017)
This work tests the hypothesis that nanoparticles of 75 at.% platinum (Pt) composition and anisotropic morphology, will outperform standard catalysts in (PEMFC) hydrogen fuel cells. A survey of the scientific literature on this topic is first presented. The synthetic strategies which were developed for the preparation of novel Pt-based binary (bimetallic) and ternary (trimetallic) nanoparticles, containing nickel (Ni), cobalt (Co) and/or vanadium (V), are then described. The synthesis protocols for solution-grown colloidal nanoparticles all required the heat-up of a chemical mixture (of metal precursors, surfactants as stabilizers, solvents and/or reductants) from room temperature to high temperatures (up to 310 °C), for thermal decomposition or thermal co-reduction. These protocols were successful in producing nanostructures of high quality, with exceptional solubility in polar solvents such as chloroform after repeated washing and drying. Detailed microstructural investigations of the synthesized nanoparticles were carried out using scanning transmission electron microscopy (STEM), TEM and X-ray diffraction (XRD). The nanoparticles were anisotropic with composition around 75 at.% Pt. Depending on the particular synthesis protocol, the as-prepared nanoparticles exhibited different morphologies, surface facets, size and structure (alloy or core-shell). To measure the oxygen reduction reaction (ORR) functionality of these nanoparticles, electrochemical measurements were conducted, including cyclic voltammetry (CV), carbon monoxide stripping voltammetry (CO-stripping) and rotating disk electrode measurements (RDE). These measurements determined (a) electrochemical surface area, (b) mass-specific activity and (c) area-specific activity; which were used to compare the performance of the synthesized nanoparticles with the performance of a standard catalyst. The synthesised nanoparticles, containing 75 at.% Pt and having anisotropic morphologies, exhibited better catalytic functionality than the standard catalysts currently in widespread use. The enhanced functionality of these alloy nanostructures is attributed to their anisotropic nature and structure (mixed or core-shell). It is shown accordingly that high surface area nanoparticles, with platinum composition around 75 at.%, are more effective than the best catalysts currently in use. Subsequently, electrochemical measurements were used to determine longevity: catalytic functionality was measured after cycling for considerably longer than the norm in nanoparticle research (5000 cycles). These measurements show a decay in catalytic activity after prolonged potential cycles, although the final value is similar to the initial value for commercial Pt catalyst. This decay is suggestive of alloying dissolution and surface facet deformation; further work is recommended.